Philosophy as a smoking pipe for elves - Matos, Junot Cornélio; Ramos, Sérgio Ricardo Vieira (Argumentos - Revista de Filosofia, 2020)
The article problematizes the context of persecution and denial of the teaching process of philosophy. It is an attempt to discredit the presence of Philosophy in school by presenting it as useless knowledge, with no use for the training of the young student. In the words of a member of the government court, it can be referred as a “pipe for elves”. The authors question what would be this "pipe" as manner of discussing the importance of Philosophy and its teaching in school educational processes; and, in this sense, it replaces the critical role of philosophizing and philosophy.